Utilization of molecular genetic techniques in support of plantain and banana improvement - Crouch, J.H.; Ortiz, R.; Crouch, H.K. (International Society for Horticultural Science, 2000)
Molecular genetic techniques may have a wide range of applications for improving the efficiency of Musa breeding and conservation. These range from analysis of genetic behaviour and structure, germplasm characterization and marker assisted selection. Restriction fragment length polymorphism (RFLP) appears to have limited application in Musa. Thus, we have concentrated on applications of the polymerase chain reaction (PCR) for Musagenome analysis. Random amplified polymorphic DNA (RAPD) techniques were assessed for fingerprinting of plantain landraces and specific somaclonal variants. Concomitantly, oligonucleotide primers have been constructed from genomic regions bordering Musa microsatellites in order to detect polymorphisms in the number of simple sequence repeats (SSR). SSR primers have been used to distinguish diverse germplasm and full-sib hybrids in both tetraploid and triploid plantain hybrid families. Furthermore, microsatellite markers have been used to demonstrate the occurrence of recombination during the formation of 2n gametes from triploid plantain and the heterozygosity of a banana accession commonly used as a true breeding genotype in genetic studies and Musa improvement programs. Finally, candidate RAPD and SSR markers for a number of important agronomic characters have been identified. The potential uses of these molecular based techniques in the fields of germplasm improvement, conservation and characterization are discussed.